Influence of Post-Peak Feed Withdrawal Rate on Egg Production by Broiler Breeders of Different Weights - Lien, R.J.; Hess, J.B. (International Journal of Poultry Science, 2009)
Broiler breeder hens are subjected to feed withdrawal as production declines after about 30 weeks of age. This study investigated effects of fast and slow feed withdrawal rates in both high and low weight hens, since body weight influences energy needs and nutrient stores. Daily allotments accounted for weight differences between high and low weight groups while decreasing 20.2 g per hen (12.8%) from peak production to 60 weeks in the slow withdrawal treatment, and 40.4 g per hen (25.6%) in the fast withdrawal treatment. From 31-60 weeks, weight gain was greatest in slow (702 g), intermediate in high-fast (351 g), and least in the low-fast treatment (219 g). Egg production began earlier and was greater in the high than low weight treatment from 23-30 weeks, was unaffected by treatments from 31-40 weeks, was greater in the slow than fast withdrawal treatment from 41-50 weeks and was greater in the low than high weight treatment from 51-60 weeks. Total production was unaffected by weight but 4.6 eggs per hen less in the fast relative to slow withdrawal treatment. The egg weight increase from 30-60 weeks was 1.4 g less in the fast relative to slow withdrawal treatment. Feed efficiency was better in the low than high weight treatment, but only marginally reduced by the fast relative to slow withdrawal treatment. These results indicate low weight breeder hens produce similar egg numbers with greater efficiency than high weight hens. In addition, doubling the typical feed withdrawal rate limits body and egg weight increases, but since it reduces egg production it only minimally improves feed efficiency.